Oleanane triterpenes with protein tyrosine phosphatase 1B inhibitory activity from aerial parts of Lantana camara collected in Indonesia and Japan. (December 2017) - Abdjul, Delfly B.; Yamazaki, Hiroyuki; Maarisit, Wilmar; Rotinsulu, Henki; Wewengkang, Defny S.; Sumilat, Deiske A.; Kapojos, Magie M.; Losung, Fitje; Ukai, Kazuyo; Namikoshi, Michio
Abstract: During the search for new protein tyrosine phosphatase (PTP) 1B inhibitors, EtOH extracts from the aerial parts of Lantana camara L. (lantana) collected at Manado (Indonesia) and two subtropical islands in Japan (Ishigaki and Iriomote Islands, Okinawa) exhibited potent inhibitory activities against PTP1B in an enzyme assay. Four previously undescribed oleanane triterpenes were isolated together with known triterpenes and flavones from the Indonesian lantana. The EtOH extracts of lantana collected in Ishigaki and Iriomote Islands exhibited different phytochemical profiles from each other and the Indonesian lantana. Triterpenes with a 24-OH group were isolated from the Indonesian lantana only. Five known triterpene compounds were detected in the Ishigaki lantana, and two oleanane triterpenes with an ether linkage between 3β and 25 were the main components together with five known triterpenes as minor components in the Iriomote lantana. The structures of previously undescribed compounds were assigned on the basis of their spectroscopic data. Among the compounds obtained in this study, oleanolic acid exhibited the most potent activity against PTP1B, and is used as a positive control in studies on PTP1B. Graphical abstract: Lntana camara L. obtained from three collected sites showed the different phytochemical profiles and gave twenty-two oleanane triterpenes and three flavones. Among them, four oleanane triterpenes were previously undescribed compounds from the Indonesian lantana. Moreover, structure-activity relationship of PTP1B inhibitory activity for the triterpenes was discussed. Highlights: Four unknown oleanane triterpenes were elucidated by their NMR data. Lantana from three collected sites displayed different phytochemical profiles. The pentacyclic triterpenes obtained in this study inhibited PTP1B activity.